Preparation process of polyimide binder, product and application
By introducing carboxyl structure and carboxyl-containing compounds into the polyimide binder to form a soft-hard segment chimeric structure, the problems of poor stability and insufficient peeling force under high temperature and high pressure conditions are solved, and a polyimide binder and positive electrode slurry with high peeling force and good thixotropy are achieved.
Patent Information
- Application Number
- CN202411740151.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
AI Technical Summary
Existing binders such as polyvinylidene fluoride are difficult to stabilize the positive electrode-electrolyte interface and positive electrode structure under high temperature and high pressure conditions, and the peeling force is limited, the process is cumbersome, and the cost is high.
By preparing soft and hard segment intermediates for polymerization, a carboxylic structure is introduced, the soft segment is set to isocyanate end capping, and the hard segment is amino end capping, and a carboxylic compound is added to the polymer to form a soft-hard segment chimeric structure, which improves the peel strength of the binder and the thixotropy and stability of the positive electrode slurry.
It significantly improves the peeling force of the polyimide binder and the thixotropy and stability of the positive electrode slurry, takes into account the peeling force and processability of the material, and reduces production costs.
Smart Images

Figure BDA0005162443800000021 
Figure BDA0005162443800000022 
Figure BDA0005162443800000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adhesives (IPC classification number: C09J), and in particular to a preparation process, product and application of a polyimide adhesive. Background Art
[0002] As a high-performance polymer material, polyimide binders have shown great application potential in many key fields such as aerospace, electronics and electrical, new energy, and automobile manufacturing due to their excellent thermal stability, chemical inertness, high strength, and excellent bonding properties. Especially in the field of new energy vehicles, polyimide binders play a key role in improving battery safety and cycle life, and have promoted the rapid development of the electric vehicle industry. Through in-depth research on the molecular structure, performance regulation, and processing technology of polyimide, its performance can be further optimized, its application range can be broadened, and new ideas and methods can be provided for the research and development of high-performance materials and devices.
[0003] Focusing on the field of new energy batteries, traditional binders such as polyvinylidene fluoride (PVDF) currently have deficiencies such as low bonding strength, easy swelling, and easy degradation, and it is difficult to effectively stabilize the positive electrode-electrolyte interface and positive electrode structure under high temperature and high pressure conditions. For example, Chinese patent CN117747824A discloses a binder for positive electrode slurry, positive electrode slurry, positive electrode sheet and sodium ion battery, using polyurethane and polyaniline as binders, instead of conventionally used polyvinylidene fluoride PVDF, to solve the current sodium ion battery positive electrode slurry polyvinylidene fluoride PVDF binder is easy to cause the slurry to gel. The problem. Chinese patent CN115286803B discloses a BAB type block copolymer, a preparation method, a binder, a positive electrode sheet, a secondary battery and an electrical device, which suppresses the dissolution of transition metals in the positive electrode active material by a block copolymer, thereby improving the cycle performance and storage performance of the battery. However, these prior arts still have problems such as limited adhesive peeling force, cumbersome process, and high cost. Therefore, it is urgent to provide a binder with high peeling strength and good processability. Summary of the invention
[0004] The first aspect of the present invention provides a process for preparing a polyimide adhesive, wherein the steps for preparing the polyimide adhesive include:
[0005] S1. Preparation of soft segment intermediates;
[0006] S2. Preparation of hard segment intermediates;
[0007] S3. Mix the soft segment intermediate, the hard segment intermediate and the carboxyl group-containing compound and react to obtain a polyimide binder.
[0008] In some preferred embodiments, the raw materials for preparing the soft segment intermediate and the hard segment intermediate both include diisocyanate.
[0009] In some preferred embodiments, the carboxyl group-containing compound contains a terminal hydroxyl group structure, and the number of hydroxyl groups in the terminal hydroxyl group structure is greater than 1.
[0010] In some preferred embodiments, the carboxyl-containing compound includes at least one of diaminobenzoic acid, dimethylolbutyric acid, dimethylolpropionic acid, polyacrylic acid, polybutenoic acid, and polyaspartic acid-polyethylene glycol-carboxyl.
[0011] More preferably, the carboxyl-containing compound includes at least one of diaminobenzoic acid, dimethylolbutyric acid, and dimethylolpropionic acid.
[0012] In some preferred embodiments, the raw materials for preparing the soft segment intermediate include: diol and diisocyanate.
[0013] More preferably, the diol comprises an aliphatic diol and / or a polyester polyol.
[0014] In some preferred embodiments, the structural formula of the aliphatic diol is:
[0015]
[0016] The value range of n is 2-10, which can be listed as 2, 3, 4, 5, 6, 7, 8, 9, 10.
[0017] Preferably, the aliphatic diol is dodecanediol.
[0018] In some preferred embodiments, the structural formula of the polyester polyol is:
[0019]
[0020] Examples of the polyester polyol include poly(1,4-butylene adipate diol) and sebacic acid-based polyester polyol.
[0021] In some preferred embodiments, the poly(1,4-butylene adipate) diol includes at least one of PBA-1000, PBA-2000, PBA-3000, PBA-4000, and PBA-5000.
[0022] In some preferred embodiments, the sebacic acid-based polyester polyol includes THCM-2800.
[0023] In some preferred embodiments, the step of preparing the soft segment intermediate in step S1 comprises: mixing and reacting a diisocyanate with a diol to obtain an isocyanate-terminated soft segment intermediate.
[0024] More preferably, the reaction temperature in step S1 is 50-65° C., and the reaction time is 0.5-3 h.
[0025] In some preferred embodiments, the number average molecular weight of the soft segment intermediate is 500-50,000; more preferably, the number average molecular weight of the soft segment intermediate is 500-20,000.
[0026] In some preferred embodiments, the raw materials for preparing the hard segment intermediate include: aromatic diamine or aromatic anhydride, and diisocyanate.
[0027] In some preferred embodiments, the aromatic diamine includes at least one of diaminodiphenylmethane, diaminodiphenyl ether, p-phenylenediamine, m-phenylenediamine, diaminodiphenyl sulfone, 3,3'-dichloro-4,4'-diaminophenylmethane, and 4,4-diamino-2,2'-bistrifluoromethylbiphenyl.
[0028] More preferably, the aromatic diamine includes diaminodiphenyl ether and / or diaminodiphenyl sulfone.
[0029] In some preferred embodiments, the aromatic anhydride includes at least one of trimellitic anhydride or terephthalic anhydride.
[0030] In some preferred embodiments, the step of preparing the hard segment intermediate in step S2 comprises: mixing and reacting diisocyanate with aromatic diamine or aromatic anhydride to obtain an amino-terminated hard segment intermediate.
[0031] More preferably, the reaction temperature in step S2 is 45-55° C., and the reaction time is 0.5-3 h.
[0032] In some preferred embodiments, the number average molecular weight of the hard segment intermediate is 500-50,000; more preferably, the number average molecular weight of the hard segment intermediate is 500-20,000.
[0033] Examples of the diisocyanate include MDI (diphenylmethane diisocyanate), TDI (toluene diisocyanate), HDI (hexamethylene diisocyanate), HMDI (dicyclohexylmethane diisocyanate), NDI (1,5-naphthalene diisocyanate), and IPDI (isophorone diisocyanate).
[0034] In some preferred embodiments, the diisocyanate is MDI.
[0035] In some preferred embodiments, the raw material addition amounts of the soft segment intermediate and the hard segment intermediate satisfy the following relationship: N1-N2=N3-N4.
[0036] Wherein N1 is the mole number of diisocyanate in the soft segment intermediate, N2 is the mole number of diol, N3 is the mole number of aromatic diamine, and N4 is the mole number of diisocyanate in the hard segment intermediate.
[0037] In some preferred embodiments, the reaction temperature in step S3 is 60-90° C., and the reaction time is 2-4 h.
[0038] More preferably, after adding the carboxyl-containing compound in step S3, diisocyanate is added and then reacted.
[0039] In some preferred embodiments, the amount of the carboxyl-containing compound added in step S3 is 0.5-25 wt % of the total mass of the mixture; more preferably 1-15 wt %.
[0040] The present invention uses soft and hard segment intermediates to carry out polymerization reaction to prepare polyimide binder, introduces carboxyl groups into the polymer structure, effectively improves the peel strength of the binder, and improves the thixotropy and stability of the positive electrode slurry. Through ingenious structural design, the soft segment intermediate is set to be isocyanate-terminated, the hard segment intermediate is amino-terminated, and the carboxyl-containing compound contains a terminal hydroxyl structure, so that polymerization reaction can occur under simple reaction conditions to obtain a soft-hard segment chimeric structure containing carboxyl groups, thereby obtaining a polyimide binder and positive electrode slurry with excellent comprehensive performance. During the exploration, it was found that the selection and dosage of carboxyl-containing polymers have an important influence on the stability and thixotropy of polyimide binders. When the dosage of carboxyl-containing polymers is low, the effect on the peeling force of the binder and the stability of the positive electrode slurry is not significant; when the dosage of carboxyl-containing polymers is high, although the peeling force of the binder meets the standard, the thixotropy time of the positive electrode slurry is too fast, which will affect the normal production of battery electrodes; after a lot of exploration, it was found that when the carboxyl-containing compound is selected from diaminobenzoic acid, dihydroxymethylbutyric acid or dihydroxymethylpropionic acid, and its addition amount is controlled to 1-15wt% of the mixture, it can have both the peeling force and thixotropy and stability of the material.
[0041] The second aspect of the present invention provides a polyimide adhesive prepared by the preparation process described above.
[0042] A third aspect of the present invention provides an application of the polyimide binder as described above, wherein the polyimide binder is applied in the fields of lithium-ion batteries, automobiles, aviation, and electronic parts.
[0043] The fourth aspect of the present invention provides a positive electrode slurry. The raw materials for preparing the positive electrode slurry include, by weight: 5-20 parts of a polyimide binder, 50-100 parts of a positive electrode active material, 0.01-0.5 parts of a conductive medium, and 10-30 parts of a solvent.
[0044] The positive electrode active material can be listed as lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMn2O4), lithium iron phosphate (LiFePO4), lithium nickel cobalt manganese oxide (NCM), lithium nickel cobalt aluminum oxide (NCA), lithium iron phosphate (LPF), lithium nickel oxide (LiNiO2), lithium manganese oxide, manganese nickel cobalt composite oxide, etc.
[0045] Preferably, the positive electrode active material is LPF.
[0046] The conductive medium may be exemplified by conductive carbon black, conductive graphite, carbon fiber, carbon nanotube, graphene, and the like.
[0047] Preferably, the conductive medium is conductive carbon black.
[0048] Examples of the solvent include N-methylpyrrolidone (NMP), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC).
[0049] Preferably, the solvent is NMP.
[0050] In some preferred embodiments, the preparation step of the positive electrode slurry includes: mixing the raw materials according to the formula amount, adding grinding media, using a homogenizer to disperse them evenly, and filtering to remove the grinding media.
[0051] The grinding media may be exemplified by zirconium beads.
[0052] Beneficial effects:
[0053] The present invention provides a preparation process, product and application of a polyimide binder, which has the following advantages:
[0054] (1) The introduction of carboxyl structure into polyimide polymer can significantly improve the peeling force of polyimide binder, as well as the thixotropy and stability of positive electrode slurry.
[0055] (2) The soft segment intermediate is terminated with isocyanate, the hard segment intermediate is terminated with amino, and the carboxyl-containing compound contains a terminal hydroxyl group or an amine structure, which can undergo polymerization under simple reaction conditions to obtain a soft-hard segment chimeric structure containing a carboxyl group. The adhesive strength of the resulting polyimide adhesive can reach above 50 N / m.
[0056] (3) During the preparation process, the carboxylic acid compound is preferably added in a ratio of 1-15wt%, which can enable the material to have a good balance between peel strength and processability. Under this condition, the peel force of the polyimide binder is greatly improved, and the obtained positive electrode slurry has suitable thixotropy, which is convenient for mass production.
[0057] (4) The raw materials for the preparation of the present invention are easily available, and the preparation method is simple and energy-saving, and high-quality products can be obtained at a relatively low cost. The technology is easy to implement and has strong practicality.
[0058] (5) The present invention has a wide range of applications, not only in positive electrode slurry, but also in the automotive, aviation, and electronic parts fields, and can give full play to the advantageous properties of polyimide polymers. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 .Schematic diagram of the reaction principle of the present invention. DETAILED DESCRIPTION
[0060] In view of the technical problems that the existing polyimide binder has limited peeling force, the thixotropy and stability of the positive electrode slurry are poor, and it is not convenient to process and produce, the present invention adopts soft and hard segment intermediates to carry out polymerization reaction to prepare polyimide binder, introduces carboxyl groups into the polymer structure, effectively improves the peeling strength of the binder, and improves the thixotropy and stability of the positive electrode slurry. Through clever structural design, the soft segment intermediate is set to be isocyanate-terminated, the hard segment intermediate is amino-terminated, and the carboxyl-containing compound contains a terminal hydroxyl structure, so that polymerization reaction can occur under simple reaction conditions to obtain a soft-hard segment chimeric structure containing carboxyl groups, thereby obtaining a polyimide binder and positive electrode slurry with excellent comprehensive performance.
[0061] Note: Unless otherwise specified, the raw materials used in the present invention are all commercially available.
[0062] Example
[0063] Example 1
[0064] This embodiment provides a preparation process, product and application of a polyimide adhesive.
[0065] The preparation steps of the polyimide adhesive include:
[0066] S1. Preparation of soft segment intermediate: 50.1 g of MDI was dissolved in 70.3 g of NMP, 20.2 g of 1,12-dodecanediol was added dropwise, and the mixture was reacted at 60° C. for 2 h to obtain an isocyanate-terminated soft segment intermediate; the solid content of the soft segment intermediate was 50 wt %.
[0067] S2. Preparation of hard segment intermediate: 40 g of diaminodiphenyl ether was dissolved in 65 g of NMP, heated to 50°C, 25 g of MDI was added dropwise, and reacted at 50°C for 2 h to obtain an amino-terminated hard segment intermediate; the solid content of the hard segment intermediate was 50 wt%.
[0068] S3. 140.6 g of the soft segment intermediate, 130 g of the hard segment intermediate, 1.35 g of dimethylolbutyric acid, and 2.3 g of MDI were mixed and reacted at 80° C. for 3 h. During the reaction, 420.5 g of NMP was added dropwise to obtain a polyimide binder.
[0069] A positive electrode slurry, the raw materials include: 10g of the above-mentioned polyimide binder, 70g of LFP (Fullin Precision), 0.1g of conductive carbon black (Cabot VXC72R), and 20g of NMP.
[0070] The preparation steps of the positive electrode slurry include: mixing the raw materials according to the formula, adding 100g of grinding media (3mm zirconium beads), dispersing them evenly using a homogenizer, and then filtering with a 50μm pore size filter to remove the grinding media, so as to obtain the positive electrode slurry.
[0071] Example 2
[0072] This embodiment provides a preparation process, product and application of a polyimide adhesive.
[0073] The preparation steps of the polyimide adhesive include:
[0074] S1. Preparation of soft segment intermediate: 50.1 g of MDI was dissolved in 70.3 g of NMP, 20.2 g of 1,12-dodecanediol was added dropwise, and the mixture was reacted at 60° C. for 2 h to obtain an isocyanate-terminated soft segment intermediate; the solid content of the soft segment intermediate was 50 wt %.
[0075] S2. Preparation of hard segment intermediate: 40 g of diaminodiphenyl ether was dissolved in 65 g of NMP, heated to 50°C, 25 g of MDI was added dropwise, and reacted at 50°C for 2 h to obtain an amino-terminated hard segment intermediate; the solid content of the hard segment intermediate was 50 wt%.
[0076] S3. 140.6 g of the soft segment intermediate, 130 g of the hard segment intermediate, 8.1 g of dimethylolbutyric acid, and 13.7 g of MDI were mixed and reacted at 80° C. for 3 h. During the reaction, 493.2 g of NMP was added dropwise to obtain a polyimide binder.
[0077] A positive electrode slurry, the raw materials include: 10g of the above-mentioned polyimide binder, 70g of LFP (Fulham Seiko), 0.1g of conductive carbon black (Cabot VXC72R), and 20g of NMP.
[0078] The preparation steps of the positive electrode slurry include: mixing the raw materials according to the formula, adding 100g of grinding media (3mm zirconium beads), dispersing them evenly using a homogenizer, and then filtering with a 50μm pore size filter to remove the grinding media, so as to obtain the positive electrode slurry.
[0079] Example 3
[0080] This embodiment provides a preparation process, product and application of a polyimide adhesive.
[0081] The preparation steps of the polyimide adhesive include:
[0082] S1. Preparation of soft segment intermediate: 50.1 g of MDI was dissolved in 70.3 g of NMP, 20.2 g of 1,12-dodecanediol was added dropwise, and the mixture was reacted at 60° C. for 2 h to obtain an isocyanate-terminated soft segment intermediate; the solid content of the soft segment intermediate was 50 wt %.
[0083] S2. Preparation of hard segment intermediate: 40 g of diaminodiphenyl ether was dissolved in 65 g of NMP, heated to 50°C, 25 g of MDI was added dropwise, and reacted at 50°C for 2 h to obtain an amino-terminated hard segment intermediate; the solid content of the hard segment intermediate was 50 wt%.
[0084] S3. 140.6 g of the soft segment intermediate, 130 g of the hard segment intermediate, 8.1 g of diaminobenzoic acid, and 13.5 g of MDI were mixed and reacted at 80° C. for 3 h. During the reaction, 493.2 g of NMP was added dropwise to obtain a polyimide binder.
[0085] A positive electrode slurry, the raw materials include: 10g of the above-mentioned polyimide binder, 70g of LFP (Fullin Precision), 0.1g of conductive carbon black (Cabot VXC72R), and 20g of NMP.
[0086] The preparation steps of the positive electrode slurry include: mixing the raw materials according to the formula, adding 100g of grinding media (3mm zirconium beads), dispersing them evenly using a homogenizer, and then filtering with a 50μm pore size filter to remove the grinding media, so as to obtain the positive electrode slurry.
[0087] Example 4
[0088] This embodiment provides a preparation process, product and application of a polyimide adhesive.
[0089] The preparation steps of the polyimide adhesive include:
[0090] S1. Preparation of soft segment intermediate: 50.1 g of MDI was dissolved in 70.3 g of NMP, 20.2 g of 1,12-dodecanediol was added dropwise, and the mixture was reacted at 60° C. for 2 h to obtain an isocyanate-terminated soft segment intermediate; the solid content of the soft segment intermediate was 50 wt %.
[0091] S2. Preparation of hard segment intermediate: 40 g of diaminodiphenyl ether was dissolved in 65 g of NMP, heated to 50°C, 25 g of MDI was added dropwise, and reacted at 50°C for 2 h to obtain an amino-terminated hard segment intermediate; the solid content of the hard segment intermediate was 50 wt%.
[0092] S3. 140.6 g of the soft segment intermediate, 130 g of the hard segment intermediate, 8.1 g of dimethylol propionic acid, and 15.1 g of MDI were mixed and reacted at 80° C. for 3 h. During the reaction, 493.2 g of NMP was added dropwise to obtain a polyimide binder.
[0093] A positive electrode slurry, the raw materials include: 10g of the above-mentioned polyimide binder, 70g of LFP (Fullin Precision), 0.1g of conductive carbon black (Cabot VXC72R), and 20g of NMP.
[0094] The preparation steps of the positive electrode slurry include: mixing the raw materials according to the formula, adding 100g of grinding media (3mm zirconium beads), dispersing them evenly using a homogenizer, and then filtering with a 50μm pore size filter to remove the grinding media, so as to obtain the positive electrode slurry.
[0095] Example 5
[0096] This embodiment provides a preparation process, product and application of a polyimide adhesive.
[0097] The preparation steps of the polyimide adhesive include:
[0098] S1. Preparation of soft segment intermediate: 50.1 g of MDI was dissolved in 70.3 g of NMP, 20.2 g of 1.12 dodecanediol was added dropwise, and the mixture was reacted at 60°C for 2 h to obtain an isocyanate-terminated soft segment intermediate; the solid content of the soft segment intermediate was 50 wt%.
[0099] S2. Preparation of hard segment intermediate: 20 g of diaminodiphenyl ether and 24.8 g of diaminodiphenyl sulfone were dissolved in 70 g of NMP, heated to 50°C, 25 g of MDI was added dropwise, and the mixture was reacted at 50°C for 2 h to obtain an amino-terminated hard segment intermediate; the solid content of the hard segment intermediate was 50 wt%.
[0100] S3. 140.6 g of the soft segment intermediate, 140 g of the hard segment intermediate, 8.1 g of dimethylolbutyric acid, and 13.7 g of MDI were mixed and reacted at 80 ° C for 3 h. During the reaction, 508 g of NMP was added dropwise to obtain a polyimide binder.
[0101] A positive electrode slurry, the raw materials include: 10g of the above-mentioned polyimide binder, 70g of LFP (Fullin Precision), 0.1g of conductive carbon black (Cabot VXO72R), and 20g of NMP.
[0102] The preparation steps of the positive electrode slurry include: mixing the raw materials according to the formula, adding 100g of grinding medium (3mm zirconium beads), dispersing evenly with a homogenizer, and then filtering with a 50um pore size filter to remove the grinding medium, so as to obtain the positive electrode slurry.
[0103] Comparative Example 1
[0104] Polyimide binder: Arkema PVDF HSV900
[0105] Positive electrode slurry: Same as Example 1; the difference is that the polyimide binder is Arkema PVDF HSV900.
[0106] Comparative Example 2
[0107] This comparative example provides a preparation process, product and application of a polyimide adhesive, and the specific implementation method is the same as that of Example 1; the difference is that, S3. 140.6 g of the soft segment intermediate and 130 g of the hard segment intermediate are evenly mixed, reacted at 80° C. for 3 h, and 406 g of NMP is added dropwise during the reaction to obtain a polyimide adhesive.
[0108] Performance Testing
[0109] 1. Peel force test:
[0110] With reference to GB / T2790-1995, the positive electrode slurries of Examples 1-4 and Comparative Examples 1-2 were subjected to a peeling force test; the test conditions were: the bonding substrate was aluminum foil, the coating thickness was 200 μm, and the test was performed after drying at 130°C.
[0111] 2. Thixotropy test:
[0112] Take the positive electrode slurry of Example 1-4 and Comparative Example 1-2, and use a BROOKFIELD rotary viscometer 63# rotor at 25°C to measure the slurry viscosity at different speeds of 1 to 60 rpm, and the slurry viscosity is 3000±500cp. Then let it stand in a vacuum environment at 25°C, and measure the viscosity at different speeds (1 to 60 rpm) every 1h. If the slurry viscosity changes significantly with the measured speed (the viscosity fluctuates between 3000 and 10000cp, the speed gradually increases, and the viscosity gradually decreases), it means that the slurry has a thixotropic phenomenon; otherwise, there is no thixotropic phenomenon. For samples with thixotropic phenomenon, the thixotropic time (unit: h) is further recorded.
[0113] 3. Cathode slurry stability test:
[0114] Take the positive electrode slurry of Examples 1-4 and Comparative Examples 1-2, place it in a vacuum environment at 25°C for 24 hours, take 0.5g of the upper slurry and the lower slurry after placement every 2 hours, and measure the mass concentration of the upper and lower slurries (at 180°C, drying for 3 hours). If the difference between the mass concentration of the lower slurry and the mass concentration of the upper slurry is greater than 1%, it is recorded as agglomeration, otherwise it is recorded as no agglomeration. For samples with agglomeration, the time when agglomeration occurs is further recorded (unit: h).
[0115] The test results are shown in Table 1 below.
[0116] Table 1
[0117]
Claims
1. A process for preparing a polyimide adhesive, characterized in that: The preparation steps of the polyimide adhesive include: S1. Preparation of soft segment intermediates; S2. Preparation of hard segment intermediates; S3. Mixing a soft segment intermediate, a hard segment intermediate and a carboxyl-containing compound, and reacting them to obtain a polyimide binder; the raw materials for preparing the soft segment intermediate and the hard segment intermediate both include diisocyanate.
2. The preparation process of the polyimide adhesive according to claim 1, characterized in that: The carboxyl group-containing compound contains a terminal hydroxyl group structure, and the number of hydroxyl groups in the terminal hydroxyl group structure is greater than 1.
3. The preparation process of the polyimide adhesive according to claim 2, characterized in that: The carboxyl-containing compound includes at least one of diaminobenzoic acid, dimethylolbutyric acid, dimethylolpropionic acid, polyacrylic acid, polybutenoic acid, and polyaspartic acid-polyethylene glycol-carboxyl; Preferably, the carboxyl-containing compound is at least one of diaminobenzoic acid, dimethylolbutyric acid and dimethylolpropionic acid.
4. The process for preparing the polyimide adhesive according to claim 1, characterized in that: The reaction temperature in step S3 is 60-90° C., and the reaction time is 2-4 hours.
5. The process for preparing the polyimide adhesive according to claim 1, characterized in that: The raw materials for preparing the soft segment intermediate include: diol and diisocyanate; The preparation step of the soft segment intermediate comprises: mixing and reacting diisocyanate with diol and diamine to obtain an isocyanate-terminated soft segment intermediate.
6. The process for preparing the polyimide adhesive according to claim 5, characterized in that: The raw materials for preparing the hard segment intermediate include: aromatic diamine and diisocyanate; The preparation step of the hard segment intermediate comprises: mixing and reacting diisocyanate with aromatic diamine or aromatic anhydride to obtain an amino-terminated hard segment intermediate.
7. The process for preparing the polyimide adhesive according to claim 1, characterized in that: The added amount of the carboxyl compound is 1-15wt% of the total mass of the mixture.
8. A polyimide adhesive prepared according to the preparation process according to claims 1-7.
9. An application of the polyimide adhesive according to claim 8, characterized in that: The polyimide binder is used in the fields of lithium-ion batteries, automobiles, aviation, and electronic parts.
10. A positive electrode slurry, characterized in that: The raw materials of the positive electrode slurry include: 5-20 parts of the polyimide binder according to claim 8, 50-100 parts of positive electrode active material, 0.01-0.5 parts of conductive medium, and 10-30 parts of solvent.
Citation Information
Patent Citations
BAB-type block copolymers, preparation methods, binders, positive electrode sheets, secondary batteries and electrical devices.
CN115286803B
Binder for positive electrode slurry, positive electrode slurry, positive plate and sodium ion battery
CN117747824A